The impact of non-commodity sovereign wealth funds' ownership on the domestic target firm performance - Nguyen Chi Hai; Nguyen Thanh Doan (Cogent Economics & Finance, 2021)
Previous research fails to investigate the impact of sovereign wealth funds (SWFs) on financial and non-financial performances of target firms. This study aims to fill the gap by using quantile regression technique on a sample of non-commodity SWFs and their target firms in five countries, namely France, Singapore, China, Malaysia and Vietnam. The research shows that non-commodity SWFs have a positive effect of increasing the financial performance for domestic target firms with relatively good performance. However, the SWFs have no significant impact on low-performing target businesses. The research findings imply that SWFs have limitations in management skills and experience and hesitate to invest in businesses with poor performance to avoid risks of bankruptcy and financial distress. The results show that the non-commodity SWFs tend to exert a negative impact on the non-financial performance of domestic target firms more strongly when the non-financial performance of the target firms is higher. Finally, these results indicate that SWFs are concerned with both financial and non-financial performances, and try to balance the two types of performance in an optimal way.
Keywords: 330; Business; Corporate Finance; financial performance; Investment & Securities; Management and Accounting; non-commodity sovereign wealth fund; non-financial performance; stakeholder theory; Vietnam